Low-grade endometrial stromal sarcoma: a case report and literature review - Zhao, Xiaojing; Chen, Chuqiao; Xie, Tingting; Wang, Liang (Frontiers in oncology, 2025)
BackgroundLow-grade endometrial stromal sarcoma (LG-ESS) is a rare malignant tumor of the female reproductive system with atypical clinical symptoms and slow progression.CaseA 44-year-old female with a history of intermittent severe dysmenorrhea, previous laparoscopic myomectomy, and uterine artery embolization (UAE) presented with rapidly enlarging pelvic masses. Imaging revealed uterine masses suggestive of leiomyomas, although an adnexal origin could not be excluded. Laparoscopy showed an irregularly enlarged uterus with widespread pelvic masses. Postoperative pathology and immunohistochemistry confirmed a diagnosis of LG-ESS with focal sex cord-like and smooth muscle differentiation. The patient underwent total hysterectomy and bilateral salpingo-oophorectomy, with subsequent recommendations for aromatase inhibitor therapy and lifelong follow-up. The 3-month post-surgery follow-up results indicated that the patient was recovering well, with no signs of recurrence.ConclusionBy reviewing the patient’s medical history, we gained new insights into the etiology, risk factors, and imaging characteristics of LG-ESS. Endometriotic lesions may serve as a source of LG-ESS. The use of morcellators and UAE in the treatment of benign uterine conditions can increase the risk of malignant tumors. Distinguishing LG-ESS on imaging can be challenging, but magnetic resonance imaging shows some suggestive features, including isointense or slightly hypointense signals on T1-weighted imaging, a mixed signal on T2-weighted imaging or a homogeneous high signal with internal hypointense bands, a high signal on diffusion-weighted imaging, and low apparent diffusion coefficient values, which may aid in differentiation.